2014
DOI: 10.1016/j.biomaterials.2014.01.064
|View full text |Cite
|
Sign up to set email alerts
|

3D printing of composite calcium phosphate and collagen scaffolds for bone regeneration

Abstract: Low temperature 3D printing of calcium phosphate scaffolds holds great promise for fabricating synthetic bone graft substitutes with enhanced performance over traditional techniques. Many design parameters, such as the binder solution properties, have yet to be optimized to ensure maximal biocompatibility and osteoconductivity with sufficient mechanical properties. This study tailored the phosphoric acid-based binder solution concentration to 8.75 wt% to maximize cytocompatibility and mechanical strength, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
467
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 747 publications
(494 citation statements)
references
References 31 publications
4
467
0
3
Order By: Relevance
“…However, it is an intensively studied biomaterial with many possibilities of therapeutic indications. Recently, Inzana et al 46 made an experimental 9-week study, in which they have showed bone healing optimization by introducing TCP scaffolds, manufactured in 3-D printers and combined to type-1 collagen.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is an intensively studied biomaterial with many possibilities of therapeutic indications. Recently, Inzana et al 46 made an experimental 9-week study, in which they have showed bone healing optimization by introducing TCP scaffolds, manufactured in 3-D printers and combined to type-1 collagen.…”
Section: Discussionmentioning
confidence: 99%
“…This system can use various materials including ceramic, metals, polymers as well as hydrogels [62][63][64][65] . The process is a 3-step process.…”
Section: Inkjet Based 3d Printer With Powder (I3dp-p)mentioning
confidence: 99%
“…However, the final products usually have weak biomechanical strength, which require high-temperature sintering to obtain structures suitable for bone tissue engineering (Seitz et al, 2005;Lu et al, 2012;Tarafder et al, 2013;Tarafder and Bose, 2014;Qian et al, 2015). Exploration of better binders is currently underway (Inzana et al, 2014). Tarafder and Bose (2014) used 3DP technology to fabricate a TCP scaffold and coated it with alendronate (AD) after sintering.…”
Section: D Printingmentioning
confidence: 99%